Performance Audit of National Disease Control Programme in Odisha (1996-2001) - CAG of India (CAG of India, 2002)
Review of implementation of the 'programme for prevention and control of diseases' covering (i) National Aids Control Programme (ii) National Programme for Control of Blindness and (iii) National TB Control Programme (NTCP) for the period from 1996-97 to 2000-2001 revealed several shortcomings. Instances of unspent funds, irregular utilisation of funds, pendency in submission of utilisation certificates, shortfall in achievement of targets, irregularities in purchase and supply of medicines, were common in all the programmes covered. Systems for monitoring and evaluation of the programmes were not in place and the programme objectives remained unachieved. In the Aids Control Programme equipment supplied to blood banks was not utilised/non-functional for 1 to 4 years. The shortfall in coverage under the Programme rendered the State's achievement figures doubtful. State Government was not able to report prevalence rate for blindness. In NTCP there were shortfalls in achievement of the targets and inaccurate reporting of data.
For the Period 1996-97 to 2000-01